Systematic Review of the Clinical Interventions for the Treatment of Asthmatic Children for Application in Saudi Arabia: Evaluation of Treatment Guidelines for Asthmatic Children in Saudi Arabia (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Background Systematic Review of the Clinical Interventions for the Treatment of Asthmatic Children for Application in Saudi ArabiaObjective The purpose of this systematic review of literature was to evaluate the efficacy of pharmacological and non-pharmacological interventions in helping develop the health standards for Asthmatic Children in Saudi Arabia as mentioned in the published studies.Methods To achieve the goal of this proposal for developing a systematic review, the bibliographic databases (including the Cochrane (CENTRAL), EMBASE PUBMEDMEDLINE and google scholar) were systematically searched for the studies related to health care system containing the data in the form of different analyses meta-analyses of RCTs (Randomized Control Trials). The search terms were combined with Boolean operators along with wild cards and truncations to broaden or narrow down the search results. Spelling variations (such as paediatric, paediatric) were also used to retrieve maximum relevant studies. The example search terms included new-born or youth AND corticosteroid or ICS or steroid or glucocorticoid or cortico-steroid or solumedrol or prednis or dexamethasone or ormethylpred or medrol or decadron or solucortef or mometoasone furoate or triamcinolone acetonide or fluticasone propionate or beclometasone or SABA or LABA or theophylline AND leukotriene modifiers AND combination inhalers AND clinical intervention AND severe or acute or exacerbated AND asthmatic children or paediatric asthma AND treatment AND emergency department or emergency settings AND Saudi Arabia AND GINA criteria AND TRACK criteria AND C-ACT method.Results Of the final 30 studies, majority of the research findings focused on the asthmatic medications and their efficacy of treatment, whereas, the rest dealt with the current guidelines being implemented in Saudi Arabia worldwide and the context of their development. All the studies were then made part of the discussion where their clinical interventions and prevention programmes were discussed in detail and pharmacological and non-pharmacological treatment guidelines were established.Conclusion All reports and documents describing the clinical trials for Inhaled and Systemic Corticosteroids, Leukotriene Modifiers, Beta Agonists, Theophylline and Combination Therapies of multiple drugs from all over the world were evaluated for developing the most effective treatment guidelines for Asthmatic children from the time of their birth to the age of 16 years for application in Saudi Arabia.